2021
DOI: 10.1590/2318-0331.262120200110
|View full text |Cite
|
Sign up to set email alerts
|

Stepped spillways with aerators: hydrodynamic pressures and air entrainment

Abstract: The possibility of damage due to the phenomenon of cavitation leads the design of stepped spillways considering maximum specific discharges of 15 to 30 m2/s, a limit considerably lower than that practiced on smooth chutes. Aerators promote the insertion of air in the flow, allowing for the increase of specific flow rates. This work analyzes the pressures on the vertical faces of the steps and the air entrainment coefficient in the flow, through an experimental study in a physical model with a stepped chute ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
(43 reference statements)
3
3
0
Order By: Relevance
“…In this region, the higher β, the higher is also P 0.1% (that is, the less negative is P 0.1% ), so the results associated with the NAT condition are more extreme (more negative) than those of the induced aeration conditions, in general. Such behavior is consistent with what was measured by Priebe (2020) and Ferla et al (2021).…”
Section: /13supporting
confidence: 93%
See 2 more Smart Citations
“…In this region, the higher β, the higher is also P 0.1% (that is, the less negative is P 0.1% ), so the results associated with the NAT condition are more extreme (more negative) than those of the induced aeration conditions, in general. Such behavior is consistent with what was measured by Priebe (2020) and Ferla et al (2021).…”
Section: /13supporting
confidence: 93%
“…Similar conclusions were also observed by Ferla et al (2021), when they evaluated experimental results of extreme negative pressures (P 0.1% , P 1% and P 5% ) on the vertical face of the steps of a spillway (α ≈ 53º) subjected to different conditions of induced aeration, compared to natural aeration. However, the results of Ferla et al (2021) identified a tendency to increase pressures in conditions where the incorporation of air in the flow was greater when compared to natural aeration.…”
Section: /13supporting
confidence: 82%
See 1 more Smart Citation
“…Air can be inserted into the flow by aerator elements such as piers and deflectors combined with an air supply system. Authors such as Dong et al (2019), Koen et al (2019), Ma & Wu (2021) and Priebe et al (2021) studied the aeration induced in stepped spillways by piers and Pfister et al (2006a), Pfister et al (2006b), Mojtaba et al (2015), Terrier (2016), Novakoski et al (2020) and Ferla et al (2021) with deflectors.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that β considers only the air entrance through the aerator elements and not the air-water changes through the free surface. Some authors who proposed equations which allows estimating this coefficient for different kinds of aerators elements are Kökpınar & Gogus (2002), Zamora et al (2008), Pfister and Hager (2010), Terrier (2016) and Ferla et al (2021). Generally, the equations proposed are a function of Froude number, aerator geometry, flow depth, mean flow velocity, or the reach of the jet.…”
Section: Introductionmentioning
confidence: 99%